ANALYSIS AND PERSPECTIVES OF RESEARCH ON THE INFLUENCE OF MICROWAVE RADIATION ON MORTARS AND CONCRETES - Ivanova, G. P.; Barsukova, S. O.; Khalymendyk, O. V.; Chumak, O. M. (Science and Transport Progress, 2019)
Purpose. In this work, we study the influence of the conditions and parameters of microwave radiation on the change in the physico-mechanical properties of building materials, in particular the problem of assessing the stability of their strength characteristics. Methodology. The following methods were used in the work: the study of the influence of microwave heating on the kinetics of the products` properties, the determination of the ultimate compression strength of mortars and concrete and comparative analysis. 5×5×5 cm cement-sand cubes made according to the SSU B V.2.7-187: 2009 were used as samples. They were cured during 28 days for grade strength acquiring. Findings. The experiment was to determine the effect of microwave radiation power and the duration of its influence on changes in the strength characteristics of dry (natural moisture) and water-saturated samples. In the course of the experiment, the uniaxial compression strength of dry and water-saturated samples previously subjected to microwave radiation (minimum, average, and maximum power) during 1-3 minutes was performed. The greatest destructive effects of microwave radiation on cement-sand samples are achieved at power values from 500 to 900 W and duration from 2 to 3 minutes. Originality. In this work, the effect of the following parameters of microwave radiation is investigated: the radiation power and the duration of its effect on the destruction process of cement-sand samples. Practical value. The established parameters of processing samples with microwave radiation facilitate the process of their destruction. This will provide a scientific basis for the use of microwave radiation in order to destroy not only concrete and other building materials, but also rocks. Also a promising direction is the study of the inverse problem – the use of microwave radiation when dissolving the concrete or mortar mixture in water, which later, after its solidification, will lead to product strength increase from these mixtures.